واقع المجلات المتخصصة في الشؤون السياحية في الجزائر دراسة تحليلية لمجلات (Tourisme et Voyages–ASSIHAR–TourismeMagazine) في الفترة الممتدة من جانفي 2019 إلى فيفري 2021 - بوعزيز نجود, عيمان سيليا (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2021)
ان الهدف من الدراسة هو تصوير وتحليل وتفسير واقع المجلات المتخصصة في الشؤون السياحية في الجزائر،وجاء التساؤل الرئيسي للدراسةكاتالي:ماهو واقع المجلات المخصصة في الشؤن السياحية في الجزائر؟ واستخدمنا في دراستنا هذه منهج المسح الوصفي للمضمون الظاهري للمواد الصحفية المنشورة عن طريق أسلوب تحليل المحتوى على عينة قصدية تتكون من 9 اعداد أي ثلاث أنواع من المجلات وهي: tourism et voyages و assihar وtourisme magazines الصادرة من جانفي 2019 الى فيفري 2021. ولعل الدراسة ذات أهمية كبيرة في الوقت الراهن خاصة مع التحولات المستجدة والتطورات الطارئة على العالم ومن خلال اطلاعنا على واقع المجلات المتخصصة في الشؤون السياحية في الجزائر على اعتبار ان المجلات المعتمدة تسعى الى تحقيق هدفها من خلال اطلاعنا على واقع المجلات المتخصصة وكذلك من خلال تغطيتها للعديد من المناطق السياحية من خلال المعطيات والنتائج توصلنا الى ان المجلات تمكنت من استعمال الجوانب الشكلية المناسبة في المواضيع التي نشرتها حول السياحة بصورة جيدة ومعتبرة ترجمت واقع السياحة. وتوصلت الدراسة الى النتائج التالية في الجانب الشكلي تبين ان الحديث والتقرير والروبورتاج الصحفي استخدمو بالدرجة الاولى في معالجة المواضيع السياحية المختلفة واظهرت الدراسة اعتمادها على الصور لان لهذه الاخير الدور الكبير في ترجمة محتوى النصوص دون قرائتها بالاضافة الجمال الذي اضافته على مستوى هذه المجلات كما اظهرت النتائج نسبة ضئيلة للاشهارقدرت ب 2% ومن اهم النتائج التي اظهرتها الدراسة طغيان اللغة الفرنسية في المجلات باعتبارها موروث استعماري واللغة الاجنبىة الاولى من حيث التداول اما من حيث تناولها للمواضيع فقد غطت المجلات التي اخذناها كعينة اكبر قدر ممكن من المواضيع في مختلف المجالات وغطت مختلف مناطق الوطن The aim of the study is to portray, analyze and interpret the reality of magazines specialized in tourism affairs in Algeria, and the main question of the study came as follows: What is the reality of magazines devoted to tourism affairs in Algeria? In this study, we used the method of descriptive survey of the apparent content of published press materials by means of a content analysis method on a purposive sample of 9 numbers of three types of magazines: tourism et voyages, assihar and tourisme magazines issued from January 2019 to February 2021. Perhaps the study is of great importance at the present time, especially with the emerging transformations and developments in the world and by informing us of the reality of specialized magazines in tourism affairs in Algeria, given that the approved magazines seek to achieve their goal by informing us of the reality of specialized magazines as well as through their coverage of many Tourist areas Through the data and results, we concluded that the magazines were able to use the appropriate formal aspects in the topics they published about tourism in a good and considered manner that translated the reality of tourism. The study reached the following results in the formal aspect, showing that the talk, the report and the press report were used primarily in dealing with various tourism topics. The study showed its reliance on images, because the latter had a great role in translating the content of texts without reading them, in addition to the beauty that they added at the level of these magazines. The results also showed a percentage of It was negligible for publicity, estimated at 2%, and one of the most important results that the study showed is the tyranny of the French language in the magazines as it is a colonial heritage and the first foreign language in terms of circulation
Keywords: الصحافة المتخصصة ، السياحة، المجلات ، الجزائر : specialized press, tourism, magazines, Algeria